2014
DOI: 10.1371/journal.pone.0105748
|View full text |Cite
|
Sign up to set email alerts
|

Complete Mitochondrial Genome of Eruca sativa Mill. (Garden Rocket)

Abstract: Eruca sativa (Cruciferae family) is an ancient crop of great economic and agronomic importance. Here, the complete mitochondrial genome of Eruca sativa was sequenced and annotated. The circular molecule is 247 696 bp long, with a G+C content of 45.07%, containing 33 protein-coding genes, three rRNA genes, and 18 tRNA genes. The Eruca sativa mitochondrial genome may be divided into six master circles and four subgenomic molecules via three pairwise large repeats, resulting in a more dynamic structure of the Eru… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
9
0
1

Year Published

2015
2015
2022
2022

Publication Types

Select...
3
3
2
2

Relationship

0
10

Authors

Journals

citations
Cited by 16 publications
(10 citation statements)
references
References 41 publications
0
9
0
1
Order By: Relevance
“…Only one complete mitochondrial genome of a gymnosperm has been published so far ( Cycas taitungensis [ Chaw et al 2008 ]), whereas complete mitochondrial genome sequences of the angiosperms Brassica maritima ( Grewe et al 2014 ), Brassica oleracea ( Grewe et al 2014 ), Capsicum annuum ( Jo et al 2014 ), Eruca sativa ( Wang et al 2014 ), Helianthus tuberosus ( Bock et al 2014 ), Raphanus sativus ( Jeong et al 2014 ), Rhazya stricta ( Park et al 2014 ) and Vaccinium macrocarpon ( Fajardo et al 2014 ) have been deposited in NCBI GenBank. Six of these projects gave details of the sample preparation, sequencing, assembly, and annotation strategy.…”
Section: Introductionmentioning
confidence: 99%
“…Only one complete mitochondrial genome of a gymnosperm has been published so far ( Cycas taitungensis [ Chaw et al 2008 ]), whereas complete mitochondrial genome sequences of the angiosperms Brassica maritima ( Grewe et al 2014 ), Brassica oleracea ( Grewe et al 2014 ), Capsicum annuum ( Jo et al 2014 ), Eruca sativa ( Wang et al 2014 ), Helianthus tuberosus ( Bock et al 2014 ), Raphanus sativus ( Jeong et al 2014 ), Rhazya stricta ( Park et al 2014 ) and Vaccinium macrocarpon ( Fajardo et al 2014 ) have been deposited in NCBI GenBank. Six of these projects gave details of the sample preparation, sequencing, assembly, and annotation strategy.…”
Section: Introductionmentioning
confidence: 99%
“…Common translocation Proto-Calepineae Karyotype (tPCK)-like ancestors were deduced to be the likely common ancestor of all current Brassiceae species that had undergone WGT and repetitive chromosomal rearrangements. Phylogenetic analysis based on 32 mitochondrial protein-coding genes suggested that Eruca sativa is closer to the Brassica species and Raphanussativus than to Arabidopsis thaliana [43]. The U's Triangle theory were accordingly revisited and extended into a multi-vertex model [42], which should include not only Raphanus, but also Eruca, Moricandia and Sinapis species as basic diploid species as suggested herein by our studies (Figure 6).…”
Section: Strong Parallel Evolution Among Brassica and Several Relativmentioning
confidence: 84%
“…Since the first mitochondrial genome was sequenced in Arabidopsis (Unseld et al, 1997), a huge number of mitochondrial genomes have been sequenced in angiosperms, such as beetroot (Kubo et al, 2000), rice (Notsu et al, 2002), rapeseed (Handa, 2003), corn (Clifton et al, 2004), wheat (Ogihara et al, 2005), Indian mustard (Heng et al, 2014) and arugula (Wang et al, 2014).…”
Section: Discussionmentioning
confidence: 99%